Unpacking the 'black box' in the relationship between pay-for-performance, employee benefits and performance - Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Joarder, Mohd Hasanur Raihan (Inderscience Enterprises Ltd., 2018)
This research examined the effect of pay-for performance (PFP) and employee benefits on employee performance with mediating effect of distributive fairness in the nexus. Through a cross-sectional approach, data were collected from a sample of 140 Nigerian employees. Partial least squares (PLS) method algorithm and bootstrap techniques were used to test the study's hypotheses. The results provided support for all the hypothesised nexuses indicating that PFP and employee benefits influence the performance of workers positively. Also, the result showed that distributive fairness mediates the relationship between PFP and employee performance, and between employee benefits and employee performance. The implication is that PFP and employee benefits can boost and enhance employee performance provided distributive fairness is perceived in the reward system that is operating in the firms. Hence, distributive fairness is an inextricable element in any reward system. Limitations and recommendations are discussed.